Gender and Spondyloarthropathy-Associated Uveitis - Wendy M. Smith (Journal of Ophthalmology)
Spondyloarthropathies encompass a group of inflammatory diseases with arthritis and other features such as enthesitis and dermatologic and gastrointestinal involvement. Up to 37% of spondyloarthropathy patients may develop uveitis which is typically bilateral asynchronous acute anterior uveitis. Spondyloarthropathies with and without uveitis are more prevalent among males; the reasons for gender imbalance are unclear. This review will focus on gender differences in the prevalence, incidence, clinical manifestations, and prognosis of uveitis associated with spondyloarthropathies.